ARFI (Acoustic Radiation Force Impulse) elastography and B-mode ultrasonography of the adrenal glands in healthy dogs of different ages - Alves, A. C. A. [UNESP]; Maronezi, M. C.; Pazzini, J. M.; Cruz, I. C. K.; Gomes, D. R.; Uchoa, A. S.; Ramos, D. J. [UNESP]; Nardi, A. B. [UNESP]; Salazar, D. V. V.; Feliciano, M. A. R. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
Sixty adrenals of 30 dogs were evaluated, divided into three groups, according to age: Group 1 = healthy youngsters (10 animals) - from one to three years old; Group 2 = healthy adults (10 animals) - four to nine years old; and Group 3 = healthy senile animals (10 animals) - older than ten years old. The experimental design was randomized, with a significance of 5%. There was a significant difference (P=0.017) in length between young and elderly dogs. The thickness of the cranial pole showed a significant difference (P=0.001) between young and adults when compared with the elderly group. The thickness of the caudal pole was not significant for adults when compared to elderly and young people. Between elderly and young, the difference was significant (P=0.024). The mean speeds differed between the groups of young and adult animals regarding the left adrenal and its cranial pole. The hardness pattern and its measurements can vary in healthy dogs of different ages, being more rigid in the cranial pole of the left adrenal in young dogs.